2018
DOI: 10.1126/scisignal.aan6480
|View full text |Cite
|
Sign up to set email alerts
|

A role for corticotropin-releasing factor signaling in the lateral habenula and its modulation by early-life stress

Abstract: Centrally released corticotropin releasing factor or hormone (extrahypothalamic CRF or CRH) in the brain is involved in behavioral and emotional responses to stress. The lateral habenula (LHb) is an epithalamic brain region involved in value-based decision making and stress evasion. Through its inhibition of dopamine-mediated reward circuitry, increased activity of the LHb is associated with addiction, depression, schizophrenia and behavior disorders. Here, we found that extrahypothalamic CRF neurotransmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 58 publications
10
107
0
Order By: Relevance
“…One investigation of presumed-adolescent male Sprague Dawley rats (125-150g) has demonstrated that CRF superfusion into the CeA results in neuronal hyperpolarization (Rainnie et al, 1992), however, this study did not directly examine synaptic transmission. A more recent study in the lateral habenula showed a CRFR1-induced reduction in GABA transmission in post-weanling rats (Authement et al, 2018), opposite of what has been established in the adults within the CeA (Bajo Sex and age influence CRFR1 function in the CeM 5 Nie et al, 2004;Roberto et al, 2010). These findings suggest a potential developmental shift in CRFR1-regulation of GABA transmission, however age and sex as biological factors have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 90%
“…One investigation of presumed-adolescent male Sprague Dawley rats (125-150g) has demonstrated that CRF superfusion into the CeA results in neuronal hyperpolarization (Rainnie et al, 1992), however, this study did not directly examine synaptic transmission. A more recent study in the lateral habenula showed a CRFR1-induced reduction in GABA transmission in post-weanling rats (Authement et al, 2018), opposite of what has been established in the adults within the CeA (Bajo Sex and age influence CRFR1 function in the CeM 5 Nie et al, 2004;Roberto et al, 2010). These findings suggest a potential developmental shift in CRFR1-regulation of GABA transmission, however age and sex as biological factors have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 90%
“…The number of APs induced by depolarization at each intensity was counted and averaged for each experimental group. AP threshold, medium after hyperpolarization (mAHP), and fast after hyperpolarization (fAHP) amplitudes were measured at the current step that was sufficient to generate the first AP/s as previously described (Authement et al, 2018). Briefly, AP threshold was measured at the beginning of the upward rise of the AP.…”
Section: Methodsmentioning
confidence: 99%
“…Again, the answer lies in the dynamics of brain circuitry. What theoretically happens in clinical depression is that persistent hyperactivity in negative (feel bad) neural circuits both directly and indirectly drives a persistent hyperactivation of a small epithalamic structure called the habenula [142][143][144][145]. Increased firing in the habenula inhibits the firing of large populations of neurons that release the "feel good" neurotransmitters serotonin and dopamine [146][147][148].…”
Section: What About Antidepressants and The Monoamine Hypothesis Of Dmentioning
confidence: 99%